Intention to use augmented reality apps for education – a behavioural study among Malaysian generation Z - Ng, Jun Yuan; Ng, Zhang Rong (2023)
Augmented reality (AR) apps have great potential in education. Compared to traditional education delivery methods, AR apps design and create interactive and immersive experiences that help learners to explore complex concepts in a more tangible way, making learning more accessible, engaging, and enthusiastic. Therefore, the usage of AR enables Gen-Z learners to become more engaged in learning. As AR is a relatively new educational technology system in developing countries like Malaysia, this study aims to investigate Gen-Z’s reaction toward the use of AR educational apps. In determining the target’s intentional usage behavior, problems that can possibly explain Gen-Z’s reluctance in using AR educational apps were explored. The following behavioral variables were identified: relative advantage, compatibility, complexity, trialability, observability, perceived value, and awareness. In solving the problems, the current research model is developed by enriching the Diffusion of Innovation (DOI) model with two additional variables: perceived value and awareness. In order to ensure the collected data in the main study can meet the reliability and validity of statistical threshold scores, the questionnaire item statements were robustly examined through pre-test and pilot studies. The item statements were amended according to the pre-test expert and pilot study participant’s feedback. The finalized questionnaire item statements that are measured by a 5-point Likert Scale were distributed to 385 Gen-Z respondents using the snowball sampling method. The main study results show that all hypotheses except the ones related to relative advantage, compatibility, complexity, and observability are related to Gen-Z’s usage intention significantly. Suitable recommendations to policymakers, academics, and future researchers are proposed based on the interpretation of hypothesis confirmation results. The project's limitations are also acknowledged, and recommendations are proposed in an attempt to minimize the study limitations and re-occurrence of non-supported hypotheses results.